PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN PADA MALAM HARI (STUDI PUTUSAN NOMOR : 707/PID.B/2025/PN TJK) - Hasan, Zainudin; Saputra, Ketut Gine (Jurnal Pahlawan, 2026)
This study analyzes the factors causing the crime of aggravated theft committed at night and the criminal liability of the perpetrator in Decision Number 707/Pid.B/2025/PN TJK concerning Erdi Sofyan bin Sunardi at the Tanjung Karang District Court. The research employs normative juridical and empirical juridical approaches, using primary data in the form of court decisions and interviews with law enforcement officials, as well as secondary data consisting of the Indonesian Criminal Code and relevant legal literature. The findings show that the defendant was legally and convincingly proven to have fulfilled the elements of Article 363 paragraph (1) points 3 and 5 of the Criminal Code, namely theft committed at night in a closed house by climbing and damaging parts of the building, resulting in losses amounting to tens of millions of rupiah. The contributing factors include planning, choice of time, proximity between the perpetrator’s residence and the victim’s house, low legal awareness, and minimal supervision. The Panel of Judges imposed a proportionate sentence of two years’ imprisonment. Keywords: Aggravated theft; Article 363 of the Criminal Code; Criminal liability.